2015
DOI: 10.1371/journal.pone.0134643
|View full text |Cite
|
Sign up to set email alerts
|

The Gut Microbiota of Wild Mice

Abstract: The gut microbiota profoundly affects the biology of its host. The composition of the microbiota is dynamic and is affected by both host genetic and many environmental effects. The gut microbiota of laboratory mice has been studied extensively, which has uncovered many of the effects that the microbiota can have. This work has also shown that the environments of different research institutions can affect the mouse microbiota. There has been relatively limited study of the microbiota of wild mice, but this has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
107
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(123 citation statements)
references
References 55 publications
11
107
2
Order By: Relevance
“…The current study revealed significant differences of the microbial community composition (the alpha diversity) in different sampling sources (the large intestine, small intestine, and feces) in two bat species ( R. sinicus and M. altarium ) although no significant variations of beta diversity were observed. These results were in line with the previous studies in mice (Gu et al., ; Pang, Vogensen, Nielsen, & Hansen, ; Weldon et al., ), pigs (Looft et al., ; Mu et al., ), and sheep (Zeng et al., ). Observed differences across the sampling sources may be caused by environmental heterogeneity in different intestinal compartments and niches, such as different oxygen exposure, pH, and substrate availability (Hao & Lee, ).…”
Section: Discussionsupporting
confidence: 91%
“…The current study revealed significant differences of the microbial community composition (the alpha diversity) in different sampling sources (the large intestine, small intestine, and feces) in two bat species ( R. sinicus and M. altarium ) although no significant variations of beta diversity were observed. These results were in line with the previous studies in mice (Gu et al., ; Pang, Vogensen, Nielsen, & Hansen, ; Weldon et al., ), pigs (Looft et al., ; Mu et al., ), and sheep (Zeng et al., ). Observed differences across the sampling sources may be caused by environmental heterogeneity in different intestinal compartments and niches, such as different oxygen exposure, pH, and substrate availability (Hao & Lee, ).…”
Section: Discussionsupporting
confidence: 91%
“…Recently, several manuscripts have questioned whether the bacterial GM of contemporary laboratory rodents is of insufficient richness and species makeup to optimally model human conditions, and proposed to use GM from wild rodents or those obtained from the pet trade 108110 . It is reasonable to conclude that the GM of laboratory mice has been simplified over the years as these rodents have been rendered free of pathogens.…”
Section: Future Directionsmentioning
confidence: 99%
“…Similarly, gut microbiota of wild mice ( Mus musculus ) are rich in diversity (Weldon et al, 2015) and dominated by Bacteroides and Robinsoniella enterotypes, a term coined by Arumugam et al (2011) in reference to clusters of microbiota communities. Following the onset of captivity, mice were found to only maintain an association with the Robinsoniella -dominated enterotype (Wang et al, 2014).…”
Section: Toward Nature's Laboratorymentioning
confidence: 99%